Schatkist van een bankier : Kunst en Architectuur bij Van Lanschot - de Koekkoek, Lidewij; Baeten, H.J.; Heemskerk, H.; van der Spek, C.N. ('s-Hertogenbosch : F. van Lanschot Bankiers N.V., 1997)
Bol, Kees ; Benner, Gerrit ; Lataster, Ger ; Brands, Eugène ; Lucebert ; Schoonhoven, Jan ; Struycken, Peter ; Visser, Carel ; van Elk, Ger ; Berkulin, Arie ; Buisman, Sjoerd ; Gudmundson, Sigurdur ; Warffemius, Piet ; van Koningsbruggen, Rob ; Gerritz, Harrie ; Haagmans, Fons ; Zijlmans, Sylvie ; van Summeren, Ton ; Drukker, Sam ; Dumas, Marlene ; Andriesse, Erik ; van Dongen, Paul ; Mulders, Marc ; van Vreden, Martin ; van Arendonk, Arjan
Nederlands
boek